Managing Agricultural Production Through Vulnerability Study (Indian Journal of Extension Education, 2017)
Agricultural vulnerability index is a tool for assessing vulnerability to various factors and is helpful in formulation of adaptation strategies to cope up with adverse impact of biological and physical factors. Agricultural vulnerability is dependent upon climatic, biological, social and infrastructural factors. The study was conducted in Madhubani and Patna districts situated in north and south Bihar respectively. In each district three villages in three different blocks with varied agro-ecological conditions were selected for the study. Focus Group Discussion (FGD) technique was adopted for getting information related to impact of biotic and abiotic factors. Total 36 FGDs consisting of male, female and mix group were conducted in 6 villages in both districts.Among the climatic factors, drought during different stages of crop growth, flood / water logging, and heat stress are thought to be adversely affecting the farming practices which are more or less recurrent in Madhubani and Patna. Farmers are sometimes also affected by erratic nature of rainfall. All the villages under study are severely to moderately affect by the disease, insect-pest or weeds. Among the social and technical factors, non-availability of quality inputs, manpower (especially, during peak period demand) and machinery are the most limiting factors for achieving desired level of yield. Agricultural vulnerability index was analyzed medium in both districts; while it was low (0.28 to 0.31) in two villages (one each in Madhubani and Patna districts). Villages with low vulnerability have lesser risk and lesser chance of failure of agricultural production. Agricultural vulnerability index in rest four villages varied from 0.36 to 0.48 that revealed medium vulnerability. In such villages one should adopt technologies, crops and strategies which can minimize risk from adverse climatic, social and biological factors for higher productivity.